Primary infertility regarding a clinical case - Hernández-González, Odalys (2023)
The increase in the prevalence of infertility has been a sensitive problem in Latin America and a global level, in Cuba represents 15 – 20 % of dissatisfaction for the couple. Following up on this problem from primary health care, and in turn, reorganizing and perfecting it constitutes a challenge for science. We present a case of primary infertility in a young couple from the Santo Domingo health area. The clinical findings of the case and the evolution until the conception of the pregnancy are described.